Movimento sindical e educação : a formação política e a qualificação técnica propostas pela Federação dos Empregados Rurais Assalariados do Estado de São Paulo-FERAESP - Lopes, Samila Bernardi do Vale (2016)
This research tevem aimed at addressing the proposed training for workers, understood as technical skills and political education, the Federation of Rural Workers of the State of São Paulo (FERAESP) next to their unions, in the context of corporate restructuring. We seek to investigate if this juncture, the challenges posed by capital - through the restructuring of the production process, the federation focused on your training proposal, the technical qualification at the expense of political education. For the development of the research, conducted a survey and literature review on the design and nature of the union, based by the Marxist framework, and also about the history of the labor movement in Brazil, both in the city and in the field. In addition, we investigated, besides the history of technical expertise in Brazil, the relationship of trade unions with education, and finally, about the history of FERAESP. For we enter deeper into the universe of this entity, especially in the field of their political and educational activities, made visits to the federation and consult pamphlets, newsletters and news, both printed, as available on the internet. We conclude that From this study we conclude that FERAESP since 1990, has been devoted to technical skills of workers, and in 2000, further intensified this proposal through the partnership with UNICA in preparing the RenovAção Program. C, however, we found that we could verify that that entity did not fail to abide political issues along with their unions. We understand, from its history and the political choices made in recent years that the path taken by the entity is a tactic to approach workers.